Fixed point theorem for generic 2-generalized hybrid mappings in Hilbert spaces - Kondo, Atsumasa (Topological Methods in Nonlinear Analysis, 2022)
We establish a fixed point theorem for a class of mappings called generic 2-generalized hybrid mappings in the setting of a real Hilbert space. Two examples of that class of mappings are presented herein. The mappings are not quasi-nonexpansive even though they have fixed points. One of these maps is even not continuous. The fixed point theorem proved in this article improves many previous works in the literature.